2021
DOI: 10.7554/elife.67381
|View full text |Cite
|
Sign up to set email alerts
|

Permeant fluorescent probes visualize the activation of SARM1 and uncover an anti-neurodegenerative drug candidate

Abstract: SARM1 regulates axonal degeneration through its NAD-metabolizing activity and is a drug target for neurodegenerative disorders. We designed and synthesized fluorescent conjugates of styryl derivative with pyridine to serve as substrates of SARM1, which exhibited large red-shifts after conversion. With the conjugates, SARM1 activation was visualized in live cells following elevation of endogenous NMN or treatment with a cell-permeant NMN-analog. In neurons, imaging documented mouse SARM1 activation preceded vin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…We identified a total of 30 rare SARM1 coding variants (missense and small in-frame deletions with allele frequencies < 0.01% in all gnomAD populations [38]) occurring exclusively in ALS patients, culled from three large publicly-accessible ALS consortia databases that include 8507 cases in total as of January 2020 [41][42][43] (Table 1). All subjects harboring rare SARM1 variants are heterozygotes.…”
Section: Enrichment Of Rare Sarm1 Variants In Als Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a total of 30 rare SARM1 coding variants (missense and small in-frame deletions with allele frequencies < 0.01% in all gnomAD populations [38]) occurring exclusively in ALS patients, culled from three large publicly-accessible ALS consortia databases that include 8507 cases in total as of January 2020 [41][42][43] (Table 1). All subjects harboring rare SARM1 variants are heterozygotes.…”
Section: Enrichment Of Rare Sarm1 Variants In Als Patientsmentioning
confidence: 99%
“…To investigate this alternate hypothesis, we generated constructs containing two mutations, either of the ALS-associated variants, i.e. SARM1 V184G or SARM1 Δ226-232 , together with E642A, a point mutation in the TIR domain that disrupts the catalytic glutamate required for SARM1 NAD + hydrolase activity and axon degeneration [23,[41][42][43][44]. In both cases, introducing E642A abolishes enzymatic activity and the detrimental effects of the constructs on cell body and axon health (Fig.…”
Section: Constitutively Active Sarm1 Variants Found In Als Patients Promote Degeneration Of Cultured Neuronsmentioning
confidence: 99%
“…To test whether SARM1 is directly activated by 3-APMN, we purified SARM1 on Strep-tag beads and incubated it with purified 3-APMN (Supplemental Fig. 2) in the presence of the pyridine conjugate PC6, a fluorescent probe of SARM1 hydrolase activity (Li et al, 2021;Zhao et al, 2019). We measured the reaction in real time by following the fluorescence output signal and found that SARM1 hydrolase activity increases with 3-APMN concentration (Fig.…”
Section: -Apmn Activates Purified Sarm1 In Vitromentioning
confidence: 99%
“…Modified from previous paper (Li et al, 2021), typically, in a mixture of 50 µl, ~200 ng of SARM1(on-beads) was mixed with 50 µM PC6, 50 µM NAD + and 0 to 100 µM of purified 3APMN. The reaction was carried out in a Bio Tek's Cytation 5 plate reader at 25 °C.…”
Section: Sarm1 Activation Assay By Pc6 Fluorescencementioning
confidence: 99%
“…In the fourth short presentation, Yongjuan Zhao (Shenzhen, China) reported the discovery of novel fluorescent probe and inhibitors of SARM1. Using the novel fluorescent probe, SARM1 enzymatic activity was imaged in live cells [ 5 ]. An analogue of nisoldipine was identified as covalent inhibitor of SARM1 reacting with cysteine residues.…”
Section: Nad Signalingmentioning
confidence: 99%